Conservation Strategy and Innovation of Indigenous Indonesian Orchids for Sustainable Practice - Khoirul Arifin, Fathur; Nuraini, Latifa; Purba, Endang Rinawati (Biotropika: Journal of Tropical Biology, 2025)
Indigenous Indonesian orchids are one of the biodiversity assets that are threatened with extinction due to habitat destruction, over-exploitation, and climate change factors. Conservation efforts have been developed to protect indigenous orchids in their natural habitat and outside their habitat. Bibliometric analysis is one of the popular tools used to analyse a number of scientific articles. VOSviewer is a method that shows that this study focuses on themes such as biodiversity, propagation technology, and ecotourism utilisation. The purpose of this study is to determine the research trend on the topic of strategy and innovation for the conservation of indigenous Indonesian orchids from year to year and to visualise research related to this topic for sustainable use. Data were collected from the SCOPUS database from 2018 to 2024 using the keywords "orchid species" OR "family Orchidaceae" OR "Orchid genus" OR "Orchid variety" AND strategy OR conservation OR innovation. The VOSviewer method was used to analyse and visualise the results. The results obtained were that the accumulation of search results in the 2018-2024 period was 355 articles. Seventy-two countries contributed to the study and were represented by 162 sponsoring institutions. This indicates that there are still many opportunities and potential from this topic that need to be developed for further research.